World Valuation Congress - Eng Ong, Seow; Yu, Shiming (Journal of property investment & finance, 2002)
This issue carries five papers selected from the 9th World Valuation Congressheld in Singapore from 26-28 April 2001. A total of 40 papers were presented, including three keynote and four plenary papers. While the main focus was onproperty valuation, a diverse range of topics was covered, reflecting the themeof the conference ''Real property valuation in a dynamic environment''.